Theories of personality - Hall, Calvin S. (Calvin Springer) 1909-1985; Lindzey, Gardner (New York John Wiley & Sons, Inc., 1970)
Covers personality theories of Sigmund Freud (psychoanalytic theory), C.G. Jung (analytic theory), Henry A. Murray (personology), Kurt Lewin (field theory), Gordon Allport, William H. Sheldon (constitutional theory), Raymond B. Cattell (factor theory), B.F. Skinner (operant reinforcement theory), Carl Rogers (self theory); also, social psychological theories, organismic theory, stimulus-response theory, existential psychology.
The nature of personality theory -- Freud's psychoanalytic theory -- Jung's analytic theory -- Social psychological theories -- Murray's personology -- Lewin's field theory -- Allport's psychology of the individual -- Organismic theory -- Sheldon's constitutional psychology -- Cattell's factor theory -- Stimulus-response theory -- Skinner's operant reinforcement theory -- Rogers' self theory -- Existential psychology -- Personality theory in perspective.
Includes bibliographical references.
Keywords: Personality